Distribution of dissolved methane in seawater from the East China Sea to the Ryukyu forearc - Toki, Tomohiro; Chibana, Hideki; Shimabukuro, Teppei; Yamakawa, Yo (Frontiers in Earth Science, 2023)
Methane is a greenhouse gas, and the East China Sea acts as a source of emissions to the atmosphere. On the other hand, the distribution of methane concentration in the Ryukyu Arc shelf and forearc region has not been clarified. Therefore, we investigated the continental slope and continental shelf areas from the Okinawa Trough to the landward side and the island shelf and forearc areas to the seaward side of the East China Sea. Higher methane concentrations were found in continental slope area and the island shelf area. The results suggest the existence of previously unreported methane sources such as cold seeps and mud volcanoes in the continental slope region and the island shelf region.